Converging 2D Nanomaterials and 3D Bioprinting Technology: State‐of‐the‐Art, Challenges, and Potential Outlook in Biomedical Applications. Issue 22 (1st September 2021) - Rastin, Hadi; Mansouri, Negar; Tung, Tran Thanh; Hassan, Kamrul; Mazinani, Arash; Ramezanpour, Mahnaz; Yap, Pei Lay; Yu, Le; Vreugde, Sarah; Losic, Dusan
Abstract: The development of next‐generation of bioinks aims to fabricate anatomical size 3D scaffold with high printability and biocompatibility. Along with the progress in 3D bioprinting, 2D nanomaterials (2D NMs) prove to be emerging frontiers in the development of advanced materials owing to their extraordinary properties. Harnessing the properties of 2D NMs in 3D bioprinting technologies can revolutionize the development of bioinks by endowing new functionalities to the current bioinks. First the main contributions of 2D NMS in 3D bioprinting technologies are categorized here into six main classes: 1) reinforcement effect, 2) delivery of bioactive molecules, 3) improved electrical conductivity, 4) enhanced tissue formation, 5) photothermal effect, 6) and stronger antibacterial properties. Next, the recent advances in the use of each certain 2D NMs (1) graphene, 2) nanosilicate, 3) black phosphorus, 4) MXene, 5) transition metal dichalcogenides, 6) hexagonal boron nitride, and 7) metal–organic frameworks) in 3D bioprinting technology are critically summarized and evaluated thoroughly. Third, the role of physicochemical properties of 2D NMSs on their cytotoxicity is uncovered, with several representative examples of each studied 2D NMs. Finally, current challenges, opportunities, and outlook for the development of nanocomposite bioinks are discussed thoroughly. Abstract : In the development of advanced materials, the unique properties of 2D nanomaterials (2D NMs) have proven to be a breakthrough. Thus, the integration of 2D nanomaterials with 3D printing has led to the development of advanced bioinks with added functionality. A comprehensive review of 2D NMs' contributions to the development of advanced bioinks is presented here.